(untitled) (Research, Society and Development, 2021)
Unintentional weight gain is emerging as a complication of the COVID-19 pandemic. Considering the popularization in the use of Internet data as an integral part of health informatics, they may be useful in the analysis and prediction of human behavior. This study analyzed the search trends of Brazilian users on weight loss strategies. An infodemiological, retrospective, quantitative study was conducted that examined data from the Google Trends Search Application tool from March/2020 to August/2021. The results revealed that the search for weight loss topics was expressive during the 17 months surveyed, almost nationwide. The states that stood out the most in the searches were Acre, Piauí, and Santa Catarina. On the other hand, users in Amazonas, Distrito Federal, Mato Grosso, Mato Grosso do Sul, and Rio de Janeiro showed less interest in the topic. The most popular weight loss strategies were dieting and fasting, while exercise and weight loss medicines showed low relative search volumes (VRBs). Aiming to investigate the other indicators and terms of interest in health, new studies on the theme are necessary to help in understanding the current and future scenario, nationally and globally, for issues involving food and nutrition conveyed on the Internet.